2016
DOI: 10.1002/ase.1621
|View full text |Cite
|
Sign up to set email alerts
|

Exploring eye movements of experienced and novice readers of medical texts concerning the cardiovascular system in making a diagnosis

Abstract: This study used the eye-tracking method to explore how the level of expertise influences reading, and solving, two written patient cases on cardiac failure and pulmonary embolus. Eye-tracking is a fairly commonly used method in medical education research, but it has been primarily applied to studies analyzing the processing of visualizations, such as medical images or patient video cases. Third-year medical students (n = 39) and residents (n = 13) read two patient case texts in an eye-tracking laboratory. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We also investigated how the processing times of the case differed between the participants who gave a correct rather than an incorrect final solution, and how the participant groups differed in making use of task-relevant and task-redundant aspects of the case. Although effective case processing plays an important role in the development of expertise, empirical studies utilizing psychophysiological research methodology in case task processing are still scarce (see, however, Berger, 2019 ; Södervik et al, 2017 ; Zumwalt et al, 2015 ; Vilppu et al, 2016 ). Better understanding of the cognitive processing of authentic-like case tasks in various disciplines and among actors with different levels of expertise enables advancing the undergraduate instruction in higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…We also investigated how the processing times of the case differed between the participants who gave a correct rather than an incorrect final solution, and how the participant groups differed in making use of task-relevant and task-redundant aspects of the case. Although effective case processing plays an important role in the development of expertise, empirical studies utilizing psychophysiological research methodology in case task processing are still scarce (see, however, Berger, 2019 ; Södervik et al, 2017 ; Zumwalt et al, 2015 ; Vilppu et al, 2016 ). Better understanding of the cognitive processing of authentic-like case tasks in various disciplines and among actors with different levels of expertise enables advancing the undergraduate instruction in higher education institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that the particular eye movement patterns correlate with success in problem‐solving (Grant & Spivey, 2003; Vilppu, Mikkila‐Erdmann, Sodervik, & Osterholm‐Matikainen, 2017). Accumulated evidence has reported that successful solvers tend to direct their gaze selectively toward the areas relevant to the task at hand (Tsai et al, 2012).…”
mentioning
confidence: 99%